Modulation Strategy and Control Range Function for Matrix Converters Without Trigonometric Functions - Igney, Jens; Hahn, Ingo (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2022, 2022)
The theory presented in this paper preserves the inherent symmetry of the matrix converter. In this way, analytically simple and computationally inexpensive formulas are derived to describe the control range and modulation of the classic 3×3 matrix converter. No trigonometric formulas need to be evaluated to verify the control range and to calculate the modulation. This is beneficial for the realization of efficient real-time program code.
CRIS-Team Scopus Importer:2022-09-02
Keywords: algorithm; control limits; control range; matrix converter; modulation strategy